Development of a yeast inhibitive assay for anionic heavy metals using the 1-(4,5-Dimethylthiazol-2-Yl)-3,5-Diphenyltetrazolium Bromide (MTT) assay - Mohd Sadli, Farah Najieha; Ammer, Masyitah Husna; Shukor, Mohd Yunus (Hibiscus Publisher, 2022)
Currently, heavy metals pollution is significantly becoming a global concern as it causes severe toxicity towards human health and the environmental condition. Intensive efforts to develop a highly sensitive, rapid, and simple toxicity assay to assess the toxic effects of heavy metals in aquatic bodies have been done. An emerging tool to solve this matter is by using microorganisms and one of them is yeast. In this study, a rapid, simple, and cost-efficient toxicity assay by using the Baker’s yeast (Saccharomyces cerevisiae) respiration assay with a tetrazolium dye (MTT) is developed as potential environmental biomonitoring tool. To achieve high sensitivity, optimization using one-factor-at-a-time (OFAT) was first carried out. The best conditions giving optimum response occurred at pH 5.8 and 30 min contact time. Molybdate and chromate exhibited exponential decay type inhibition curves with calculated half maximal inhibitory concentration, IC50 of 1.137 mg/L for molybdate and 1.247 mg/L for chromate. The Limits of detection (LOD) were 0.313 mg/L and 1.247 mg/L for molybdate and chromate, respectively. The newly developed assay can help in monitoring heavy metals pollution in rivers and agricultural areas.